Hydraulic fracturing wastewater treatment by coagulation-adsorption for removal of organic compounds and turbidity. Issue 2 (June 2016) - Rosenblum, James S.; Sitterley, Kurban A.; Thurman, E. Michael; Ferrer, Imma; Linden, Karl G.
Graphical abstract: Highlights: Frac waters from the same formation can have vast differences in water quality. Metal salts (5 ppm) can reduce turbidity and hydrocarbon levels of frac waters. Powder activated carbon can sorb PEGs and hydrocarbons in frac waters. Coagulation-adsorption can reduce turbidity, DOC, PEGs, and TPH in frac waters. Abstract: Waters produced from fracturing operations in the oil and gas industry are a complex mixture of fracturing fluids and formation water. Closing the water cycle loop in this industry depends on the effective reuse of these wastewaters, and therefore treatment. This study investigated the application of chemical coagulants and powdered activated carbon (PAC) to reduce turbidity, dissolved organic carbon (DOC), total petroleum hydrocarbons (TPH), and polyethylene glycols (PEGs) in four hydraulic fracturing wastewaters. Jar tests were performed to evaluate both the PAC and coagulants. Treatment goals were operationally defined targeting 90% reduction of turbidity, PEGs, and TPH. PAC was found to be effective at removing both PEGs and TPH from the wastewaters, but would not settle without the addition of a coagulant. Ferric chloride achieved a 90% reduction in turbidity at a lower dose than aluminum chlorohydrate, in the presence and absence of PAC. The optimized coagulant dose by itself had little to no effect upon concentrations of DOC and PEGs, while greater than 80% removal of TPH, a minor component of DOC, was observed in three of the waters. PAC at 1000 mg L −1 achieved greater than 80% reductions of the total ion chromatogram, while DOC removals were from 9.5 to 48.3%. These results suggest that coagulation with ferric chloride at doses as low as 5 mg L −1 is an effective process for turbidity and TPH reduction in hydraulic fracturing wastewaters, and when coupled with PAC can also remove DOC and targeted organic contaminants such as PEGs.